New structural motifs in metallaborane chemistry. Synthesis, characterization, and solid-state structures of (Cp*W)(3)(mu-H)B8H8,(Cp*W)(2)B7H9, and (Cp*Re)(2)B7H7 (Cp*=eta-C5Me5) - Weller, A; Shang, M; Fehlner, T (1999)
Hydrogen loss from the 7 skeletal electron pair (sep) nido 2-Cp*H3WB4H8, 1 (Cp* = η-C5-Me5), the metal analogue of pentaborane (9), has been examined as a potential source of unsaturated, reactive species. Pyrolysis of 1 leads to 6 skeletal electron pair (Cp*W)2B5H9, 2 (45%), 7 sep Cp*3W3(μ-H)B8H8 3 (19%), and 7 sep (Cp*W)2B7H9) 4 (low yield), whereas photolysis gives 2 (52%) and 4 (7%). Compound 2 is known, and 3 and 4 have been spectroscopically and crystallographically characterized. Further, the isoelectronic and nearly isostructural analogue of 4, (Cp*Re)2B7H7, 5, has been prepared from the reaction of Cp*ReCl4 and BH3THF in 66% yield. It is demonstrated that 3 exhibits a skeletal structure corresponding to a highly capped W3 bonded triangle and is analogous to a known multinuclear Ru11 cluster with a hexagonal close packed metal core. As such it constitutes an example of a closed, boron-rich metallaborane cluster with (n - 4) sep. Likewise, it is shown that 4 and 5 possess unusual structures and constitute examples of closed metallaborane clusters with (n - 2) sep. Fenske-Hall MO calculations show that the observed cluster shapes are appropriate for the observed sep's. These two new cluster types demonstrate that transition metal fragments can be used to manipulate the cluster bonding network of a borane, effectively collapsing a single cage into a more closely packed network.